Hubungan antara Usia dan Jenis Kelamin dengan Tipe Histopatologi Karsinoma Nasofaring - Melvern, Bryan; Karlowee, Vega; Dewi Kusuma Astuti, Meira (Majalah Patologi Indonesia, 2022)
BackgroundNasopharyngeal carcinoma (NPC) is a malignancy with a high incidence in Indonesia. Recent studies had found several factors that influence the incidence and prognosis of NPC including age, sex, and histopathological type. This study aimed to determine the relationship between age and sex with the histopathological type of NPC.MethodsSubjects were NPC patients diagnosed by the Anatomical Pathology Department of Dr. Kariadi General Hospital Medical Center (RSUP Dr. Kariadi) from 1st January 2017-31st December 2019. Data were collected from the medical record. The relationship between age and sex with the histopathological type of NPC was examined. ResultsThere were 201 NPC patients during 2017-2019 in RSUP Dr. Kariadi. The highest number of NPC incidence was in the range of 54-59 years old. There were more males than females at the ratio of 2.24:1. Undifferentiated non-keratinizing cell carcinoma type NPC was the most common type (90.5% of NPC patients), followed by differentiated non-keratinizing cell carcinoma and squamous cell carcinoma consecutively. Both age and sex had no significant relationship with the histopathological type of NPC (p>0.05).ConclusionThere was no relationship between age and sex with the histopathological type of NPC.